Clinical utility of anti-cyclic citrullinated peptid and rheumatoid factor in chronic hepatitis B virus infection - Gokhan Sargin; Altay Kandemir (Indian Journal of Rheumatology)
Background: It is necessary to distinguish whether musculoskeletal symptoms are associated with rheumatic diseases or hepatitis virus infection. Rheumatoid factor (RF) and anti-cyclic citrullinated peptide (anti-CCP) may be detected in rheumatic diseases and also during infections. The objective of this study was to evaluate the clinical utility of anti-CCP and RF in patients with chronic hepatitis B virus (HBV) infection. Methods: Ninety-seven patients with chronic HBV infection, 35 patients with rheumatoid arthritis (RA), and 30 healthy controls were included in the study. HBV-DNA, hepatitis B e antigen, anti-HBe, RF, and anti-CCP were evaluated. Results: The rates of positivity for RF and anti-CCP were 14.4% and 4.1% respectively in patients with chronic HBV infection. Arthritis was present in 7 of 97 patients with chronic HBV infection. There was a statistically significant difference for anti-CCP positivity but not for RF positivity between patients with arthritis and without arthritis. No correlation was found between RF and anti-CCP, HBV-DNA, anti-CCP, and HBV-DNA in patients with HBV infection. Conclusions: Anti-CCP positivity was a determinant for polyarthritis in the context of HBV infection. It appears to be a more reliable parameter than RF in differentiating arthritis and nonarthritis group in patients with HBV infection.